Analysis and Development of 3d Animation and It’s Usage as Environment in Horror Short Movie - Jimmy Pratama; Indo Dicaprio Pratama (IJISTECH (International Journal of Information System and Technology), 2022)
The development of CGI in the world of multimedia can be said to have reached the highest point where the tools used can be reached by a wide audience. CGI, which has no limitations on what is included, has the potential to be used in many fields. The use of CGI such as 3D animation has become popular because of the flexibility it provides in the world of cinematography. To produce a film, a budget is needed to meet the crucial needs so that a shot can be fulfilled. However, not all productions have that budget. Then 3D animation can be an alternative to assist filmmakers in making a film, either in a whole or partially. In this research, the writer will produce a short live-action horror film by combining a 3D environment as one of the supporting shots. The research method to be used is Research & Development, starting with semiotic analysis and followed by the MDLC (Multimedia Development Life Cycle) approach. Semiotic analysis will be carried out on 10 horror films included in the ranking by the Box Office by analyzing the aspects of Lighting, Perspective, Color and Property. The 3D animation development will be accompanied by the film production process. After the finalization of the film, testing will be carried out in the form of media expert testing and publication on the UIB Information Systems Study Program's Youtube channel. The result of the research will be a short horror film with 3D animation applied as a supporting shot to the film.